Clinical Profile and Outcome of Pediatric Mitochondrial Myopathy in China - Hu, Chaoping; Li, Xihua; Zhao, Lei; Shi, Yiyun; Zhou, Shuizhen; Wang, Yi (Frontiers in Neurology, 2020)
Introduction: Mitochondrial myopathy in children has notable clinical and genetic heterogeneity, but detailed data is lacking. Patients and Methods: In this study, we retrospectively reviewed the clinical presentation, laboratory investigation, genetic and histopathological characteristics, and follow-ups of 21 pediatric mitochondrial myopathy cases from China. Results: Twenty-four patients suspected with mitochondrial myopathy were enrolled initially and 21 were genetically identified. Fourteen patients were found to harbor mitochondrial DNA point mutations (14/21, 66.7%), including m.3243A>G (9/15, 60%), m.3303C>T (2/15, 13.3%), m.3302A>G (1/15, 6.7%), m.3250T>C (1/15, 6.7%), m.3251A>G (1/15, 6.7%), of whom 12 patients presented with progressive proximal mitochondrial myopathy (12/14, 85.7%). Three patients revealed large-scale deletion in blood or muscle tissue (3/21, 14.3%), presenting with Kearns-Sayer syndrome (1/3, 33.3%) or chronic progressive external ophthalmoplegia (2/3, 66.7%). Four patients were found to harbor pathogenic nuclear gene variants (4/21, 19.0%), including five variants in TK2 gene and two variants in SURF1 gene. During the follow-ups up to 7 years, 10 patients developed cardiomyopathy (10/21, 47.6%), 13 patients occurred at least once hypercapnic respiratory failure (13/21, 61.9%), six experienced recurrent respiratory failure and intubation (6/21, 28.6%), eight patients failed to survive (8/21, 38.1%). With nocturnal non-invasive ventilation of BiPAP, three patients recovered from respiratory failure, and led a relative stable and functional life (3/21, 14.3%). Conclusion: Mitochondrial myopathy in children has great clinical, pathological, and genetical heterogeneity. Progressive proximal myopathy is most prevalent. Mitochondrial DNA point mutations are most common. And respiratory failure is a critical risk factor of poor prognosis.